Juridical Analysis of Banking Authority In Blocking Accounts Indicated For Online Gambling: The Conflict Between The Prudential Principle and Customer Protection - Simanjuntak, Jimmy (Indonesian Journal of Law and Justice, 2026)
This research examines the juridical clash between the mandatory authority of banks to block suspicious accounts and the constitutional rights of customers to legal certainty and property protection. Utilizing a normative legal research method with statutory and conceptual approaches, this study analyzes the implementation of Law Number 8 of 2010 and POJK Number 8 of 2023. The findings reveal that heavy reliance on automated Artificial Intelligence (AI) monitoring systems creates a significant risk of "false positive" identifications, which often lack transparent verification mechanisms. Although banks possess the legal basis for account blocking as an ex-officio obligation, the current "block first, verify later" procedure frequently ignores the prudential guarantees of the Banking Law and consumer protection principles. This research concludes that a reconstruction of internal banking regulations is essential to integrate a "Right to be Heard" mechanism, ensuring that preventive measures comply with the due process of law. Implementing standardized, transparent procedures and human oversight is crucial to balancing financial system stability with the protection of well-intentioned customers.